Securitisation versus Bank Loans - BOURAS, Ahmed; BOUDAH, Abdeldjalil (Journal of Human Sciences, 2005)
Today, the world of finance is becoming more complex than ever before. For instance, the rapid evolution of capital markets in recent years has shown an outstanding interest for moving to new areas of innovative finance. In contrast to the traditional ways of finance, banking system domination, as it was in the 1970s, is becoming critical especially for loans facilities.This paper discusses the securitisation issue in comparison with bank loans. The asset backed securitisation (ABS) constitutes a real challenge that banks have to face. This situation oblige banks either succeed in restructuring their activities and is adopting the new instruments emerging from the market, or stay away from the development and the sustainability in the market